Equity research - Dimpomar, Lda.: case study - Brejo, João Miguel Faustino (2018)
The purpose of this thesis is to assess the value of Dimpomar, a privately owned company. In order to reach reasonable results and perform the valuation, the theoretical background was first presented regarding the several valuation methods, followed by a company presentation, industry analysis and the analysis of the financial indicators and situation of the company. The valuation methods used in order to reach the enterprise value, firm value, equity value and price per share value were the Discounted Cash Flow and the Relative Valuation (Multiples). The fact that these two methods were applied, allowed the comparison of Dimpomar with the peer group, having more arguments to justify the obtained value of Dimpomar, which was an enterprise value of 13,784,962€ and a price target of 177.4€. To conclude, this work provides a solid base of analysis for a possible exit through an IPO (initial public offer).